Peningkatan Hasil Belajar Peserta Didik Melalui Model Pelatihan Kooperatif Tipe STAD (Student Teams Achievement Division) - Ike Meylani Nur Sholikah; Anik Kirana; Fitria Indahwati (CV. Alim's Publishing, 2024)
Employing the syntax of the Cooperative Education Model more especially, the School Teams Achievement Departments (STAD) type this study intends to enhance students' learning results. There are three phases to this study's methodology, which is based on Classroom Action Research (CAR): pre-cycle, cycle 1, and cycle 2. Participating in this study were 37 students in their last year of high school at SMA Negeri 9 Surabaya in 2023–2024. Students' mathematical learning outcomes show a substantial improvement, according to the data. With each cycle, students' performance improved. Mastery was attained by 32.4% of students in the pre-cycle, 43.2% in cycle I, and 62.1% in cycle 2. This research provides strong evidence that the STAD type of collaborative education model improves students' performance in eleventh grade.